Effects of exercise and genetics on skeletal muscle lipid metabolism with focus on the localization and association of lipid droplets, mitochondria ja PLIN5 - Adeniran, Ajani Anuoluwapo (2018)
Low exercise capacity has been identified as a stronger predictor of morbidity and mortality relative to other commonly reported risk factors. Substrate metabolism, especially lipid storage, lipolysis and transportation in the skeletal muscles is strongly linked to aerobic capacity. The physical topographical properties of some myocellular particles and or organelles such mitochondria, lipid droplets (LDs) and perilipine-5 (Plin5) proteins in the skeletal muscle tissues have been implicated in the onset of most metabolic diseases and may also predict overall physical capacity. We tested the effect of innate high aerobic capacity (genetics) and acquired aerobic capacity (voluntary running) on the number, location and colocalization of the aforementioned particles in the gastrocnemius muscle cells, between the low and high capacity runner rats.